The risk factors of low anterior resection syndrome after colorectal cancer surgery: A retrospective study of 566 patients in a single institution in China - Ri, HyokJu; Kang, HaoNan; Xu, ZhaoHui; Kim, KunHyok; Ren, YanYing; Gong, ZeZhong; Chen, Xin (Frontiers in Surgery, 2022)
Purpose: This study aims to identify the independent risk factors in the low anterior resection syndrome (LARS) after surgery for colorectal cancer (CRC). Method: This was a retrospective, single-institution study in the Second Affiliation Hospital of Dalian Medical University, China. Patients underwent sphincter-preserving low anterior resection with total or partial mesorectal resection (with or without protective ileostomy) and completed a self-filled questionnaire over the phone to assess postoperative bowel dysfunction from January 2017 to December 2019. The predictors of LAR were evaluated using univariate and multivariate analyses. Result: The study population was 566 patients, 264 (46.64%), 224 (39.58%), and 78 (13.78%) patients with no, minor, and major LARS, respectively. In the univariate analysis, independent factors such as tumor location and size, anastomotic height, protective ileostomy, post-operation chemoradiotherapy, tumor T stage, lymphatic nodal metastasis classification, surgery duration, and time interval for closure of stoma were significantly associated with LARS points while we found the tumor T stage and lymphatic nodal metastasis classification as the new independent risk factors compared with the last decade studies. In the multivariate analysis, factors such as low and middle tumor location and protective ileostomy, and post operation treatment, nodal metastasis classification were the independent risk factors for major LARS. Conclusion: The new independence risk factors were tumor T stage and lymphatic nodal metastasis status in univariate analysis in our study, with anastomotic height, low and middle tumor location, protective ileostomy, post-operation chemoradiotherapy, nodal metastasis status increasing LARS point in multivariate analysis after surgery for CRC.